Value-Based Cooperative Learning in Islamic Education: Integrating TGT, Islamic Values, and Student Engagement - Pohan, Nurainun Matauli; Khairuddin, Khairuddin (Al-Ishlah: Jurnal Pendidikan Islam, 2025)
Background: Islamic Religious Education (PAI) often struggles to foster student engagement, as teacher-centered instruction tends to limit participation and enthusiasm. In pluralistic societies such as Indonesia, this challenge is compounded by the need to integrate Islamic values with local wisdom and religious moderation. Cooperative learning models like Team Games Tournament (TGT) have shown promise in promoting collaboration, yet their affective impact on enthusiasm in Islamic education remains underexplored. Research Objectives: This study aims to examine the effect of the TGT learning model on students’ enthusiasm for learning PAI. Specifically, it seeks to test whether TGT enhances cognitive, affective, and behavioral dimensions of enthusiasm while embedding Islamic values, local wisdom, and principles of religious moderation. Methods: A quantitative experimental approach was employed using a one-group pretest–posttest design. The participants were 29 ninth-grade students at SMP Sinar Husni Medan, selected through purposive sampling. Data were collected using a validated 25-item enthusiasm scale covering three dimensions and analyzed with descriptive statistics, Shapiro–Wilk and Levene’s tests, paired-sample t-tests, and Cohen’s d effect size. Results: Findings indicate a statistically significant improvement in enthusiasm after TGT implementation (t = 8.87, p < 0.001; Cohen’s d = 0.78). Gains were strongest in affective enthusiasm (+8.5%), followed by cognitive (+6.1%) and behavioral (+5.7%) dimensions. These results confirm that TGT not only enhances engagement but also enables students to practice values of shura, ukhuwah, and ta‘awun through cooperative interaction, complemented by local wisdom such as dalihan na tolu. Conclusions: The study concludes that TGT significantly improves enthusiasm in PAI by fostering positive emotions, participation, and cultural relevance. Theoretically, it contributes a Value-Based Cooperative Learning Framework that integrates Islamic ethics, local wisdom, and religious moderation into cooperative pedagogy. Practically, the findings suggest that TGT can revitalize Islamic education in pluralistic societies and inspire future comparative studies in both Muslim-majority and minority contexts.